2012
DOI: 10.4103/2230-8210.93776
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of emphysematous pyelonephritis

Abstract: Emphysematous pyelonephritis, though uncommon, is a severe necrotizing kidney infection common in patients with diabetes. Surgical treatment has been advocated as the treatment of choice in most of the patients. We present the clinical course of an elderly lady who presented with emphysematous pyelonephritis and was successfully managed with medical treatment despite the presence of adverse prognostic factors like acute renal failure and thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…1,8 Emphysematous pyelonephritis should be suspected in immunosuppressed patients or in patients with abnormal immune response, inadequate tissue perfusion, or poorly controlled diabetics. 2,4,5 Females are more likely to suffer a emphysematous pyelonephritis; although in renal transplantation, males are more likely to suffer. 5,6 Another issue to consider is the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,8 Emphysematous pyelonephritis should be suspected in immunosuppressed patients or in patients with abnormal immune response, inadequate tissue perfusion, or poorly controlled diabetics. 2,4,5 Females are more likely to suffer a emphysematous pyelonephritis; although in renal transplantation, males are more likely to suffer. 5,6 Another issue to consider is the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, individual assessments yield better results. 2,4,5,7,8 We report a case of emphysematous pyelonephritis in a renal transplant recipient. We also review the other reported cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However there are growing reports of successful medical treatment of EPN. [12][13][14][15] According to these reports, our case could be considered treatable by antibiotics alone partly because of the rapid diagnosis and the adequate therapy provided.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients remain on antibiotic therapy after intervention and the duration reported ranges from 10 days to 30 days depending on severity of the illness (Arsene et al, 2014). Oral antibiotics may be continued afterwards for one to three months (Best et al, 1999;Jain et al, 2000;Laway et al, 2012;Tahir et al, 2000). There are currently no established guidelines for recommended duration of antibiotics for EPN.…”
Section: Discussionmentioning
confidence: 99%